SNP Microarray in FISH Negative Clinically Suspected 22q11.2 Microdeletion Syndrome - Ashutosh Halder; Manish Jain; Amanpreet Kaur Kalsi (Scientifica)
The present study evaluated the role of SNP microarray in 101 cases of clinically suspected FISH negative (noninformative/normal) 22q11.2 microdeletion syndrome. SNP microarray was carried out using 300 K HumanCytoSNP-12 BeadChip array or CytoScan 750 K array. SNP microarray identified 8 cases of 22q11.2 microdeletions and/or microduplications in addition to cases of chromosomal abnormalities and other pathogenic/likely pathogenic CNVs. Clinically suspected specific deletions (22q11.2) were detectable in approximately 8% of cases by SNP microarray, mostly from FISH noninformative cases. This study also identified several LOH/AOH loci with known and well-defined UPD (uniparental disomy) disorders. In conclusion, this study suggests more strict clinical criteria for FISH analysis. However, if clinical criteria are few or doubtful, in particular newborn/neonate in intensive care, SNP microarray should be the first screening test to be ordered. FISH is ideal test for detecting mosaicism, screening family members, and prenatal diagnosis in proven families.